1986
DOI: 10.1111/j.1095-8649.1986.tb05152.x
|View full text |Cite
|
Sign up to set email alerts
|

The food habits of four small‐sized species of Mormyridae from the floodplain pools of the Sokoto‐Rima river basin, Nigeria

Abstract: The diet of four species of the family Mormyridae. commonly found in the floodplain pools of the Sokoto-Rima river basin, Nigeria, is described. All four species are small-sized and show a degree of food overlap. Evidence is presented, however, that resource partitioning occurs enabling co-existence of the species in a habitat where food resources become increasingly limited after the cessation of the rains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The present study explores seasonal and size-related patterns of resource exploitation within the piscivore guild of a diverse neotropical fish community. Although varying greatly in both duration and breadth of taxonomic comparison, several recent studies have shown marked resource partitioning among tropical fishes (Angermeier & Karr 1983, Power 1983, Moyle & Senanayake 1984, Schut et al 1984, Watson & Balon 1984, Araujo-Lima et al 1986, Hyslop 1986, Prejs & Prejs 1987, Nice & Taphorn 1988. Fish populations frequently are size structured due to small hatching or neonate size and continuous growth.…”
Section: Introductionmentioning
confidence: 99%
“…The present study explores seasonal and size-related patterns of resource exploitation within the piscivore guild of a diverse neotropical fish community. Although varying greatly in both duration and breadth of taxonomic comparison, several recent studies have shown marked resource partitioning among tropical fishes (Angermeier & Karr 1983, Power 1983, Moyle & Senanayake 1984, Schut et al 1984, Watson & Balon 1984, Araujo-Lima et al 1986, Hyslop 1986, Prejs & Prejs 1987, Nice & Taphorn 1988. Fish populations frequently are size structured due to small hatching or neonate size and continuous growth.…”
Section: Introductionmentioning
confidence: 99%
“…The young stages of fishes which are particularly in need of zooplankton and other small fauna besides plants, have, with few exceptions adapted to living in the shallow littoral of lakes and reservoirs (Stewart, 1988;Robotham, 1990). Newly flooded shallows of river floodplains (Balogun, 1986;Green, 1985) or floodplain pools (Hyslop, 1986). However juveniles may move temporarily into the pelagic in search of food or to avoid predators.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant freshwater fish fauna of the northern Nigeria region is that of the flood-plain. The biology of the fish species predominant there has received greater attention (Holden, 1963;Hyslop, 1986Hyslop, , 1987. The Kandole Shela, in contrast to the major rivers of the Sokoto area, does not undergo extensive horizontal flooding, due mainly to the diversion of water for irrigation purposes and to the relatively steep gradient of the stream which encourages rapid discharge during periods of rainfall.…”
Section: Discussionmentioning
confidence: 99%